Ten-year determination of atmospheric phosphorus deposition at three forested sites in Japan. (15th February 2020) - Chiwa, Masaaki
Abstract: Atmospheric phosphorus (P) deposition is an important component for understanding the dynamics of natural and semi-natural ecosystems. However, information about atmospheric P deposition is limited. Here, we show the long-term atmospheric P deposition at three forested sites, a suburban forest (S), rural forest (R1), and northern rural forest (R2) in Japan for 10 years from 2009 to 2018. Approximately 200 samples of bulk precipitation at each site were collected during the study period and total P (TP) was analyzed in addition to major ions. Annual TP deposition at sites S, R1, and R2 was 0.28 ± 0.06, 0.21 ± 0.05, and 0.12 ± 0.04 kg P ha −1 yr −1, respectively, and were large enough to affect P budgets in a forested watershed. Principal component analyses indicated that biogenic sources are the primary contributor to atmospheric P at rural forest sites, whereas anthropogenic sources may have a larger effect on atmospheric P at suburban forest site. Annual TP deposition at site S significantly decreased over the past decade. The significant relationship between annual TP deposition and annual nitrogen deposition at site S indicates that the decrease in TP deposition could be caused by a decrease in anthropogenic emissions. Graphical abstract: Image 1 Highlights: P deposition was large enough to affect P budgets in a forested watershed. Biogenic sources were a major contributor to P deposition in rural forests. Anthropogenic sources may also contribute to P deposition in suburban forests. P deposition decreased in a suburban forest over the past decade. Decreases in P deposition could reflect decreases in anthropogenic emissions.